Rs6922269 marker at the MTHFD1L gene predict cardiovascular mortality in males after acute coronary syndrome - Hubacek, J A; Staněk, V; Gebauerová, M; Poledne, R; Aschermann, Michael; Skalická, H; Matoušková, J; Kruger, A; Pěnička, M; Hrabáková, H; Veselka, J; Hájek, P; et al. (Molecular biology reports, 2015)
Myocardial infarction (MI) is the leading cause of death in industrialized countries. All the traditional risk factors for MI are responsible for approximately 50% of cases of MI cases. Attention therefore has recently focused on genetic variants that are not associated with conventional risk factors. One of them is the marker rs6922269, which has been suggested as a risk factor for development of MI in Western populations. We analyzed the relationship between rs6922269 variant on MTHFD1L gene and (i) risk of the acute coronary syndrome (ACS) in the Czech population and (ii) mortality in 7 years follow up. Rs6922269 (G>A) variant was analyzed (CR 99.3% for patients and 98.0% for controls) by PCR-RFLP in consecutively examined 1614 men and 503 women with ACS (age below 65 years) and in population-based controls--1191 men and 1368 women (aged up to 65 years). ANOVA and Chi square were used for statistical analysis. The genotype frequencies were almost identical (P=0.87) in the ACS patients and in controls and no differences were observed, if males (P=0.73) and females (P=0.93) were analysed separately. In addition, rs6922269 polymorphism was not associated with the classical risk factors (dyslipidemia, hypertension, obesity, smoking, diabetes) in control population. Cardiovascular mortality was significantly higher in males, carriers of the AA genotype (P<0.001, OR 2.52, 95% CI 1.40-4.55, for AA vs. +G). We conclude, that rs6922269 variant at MTHFD1L gene could be an important prognostic factor for cardiovascular mortality in patients after ACS.
Keywords: dospělí; Acute Coronary Syndrome; Female; Multienzyme Complexes; polymorfismus délky restrikčních fragmentů; Adult; ženské pohlaví; jednonukleotidový polymorfismus; methylentetrahydrofolátdehydrogenasa (NADP); Formate-Tetrahydrofolate Ligase; lidé; Polymorphism, Single Nucleotide; Polymorphism, Restriction Fragment Length; Risk Factors; Methylenetetrahydrofolate Dehydrogenase (NADP); multienzymové komplexy; Male; Aged; formiáttetrahydrofolátligasa; Aminohydrolases; aminohydrolasy; rizikové faktory; Myocardial Infarction; lidé středního věku; senioři; akutní koronární syndrom; mužské pohlaví; Middle Aged; infarkt myokardu; Humans